The Role of New Pulmonary Artery Wedge Pressure Formula to Predict Diastolic Dysfunction in Obstructive Sleep Apnea - Telly Kamelia; Lukman Hakim Makmun (Acta Medica Indonesiana, 2023)
Background: Heart failure (HF) is a common condition with high morbidity and mortality  in  Obstructive Sleep Apnea (OSA), especially in obese patient. The causes of HF are often abnormal conduction pathways, pump filling and/or heart valves. Right heart catheterization using Swan-Ganz catheter remains the gold standard to determine pulmonary hemodynamics, but it is costly and invasive. Herein, we propose a new formula for non-invasive Pulmonary artery wedge pressure (PAWP) measurement using tissue Doppler echocardiography. The purpose of this research is to explore the correlation between the new formula to calculate PAWP to predict diastolic dysfunction in OSA patients. Methods: A cross-sectional study was conducted in Jakarta, in March until October 2021. Eighty-two subjects were enrolled in the study, consist of 34 females and 48 males. All subjects underwent polysomnography and tissue Doppler echocardiography. Noninvasive measurement of PAWP were obtained from combined assessment of E/e’ and left atrial parameters. Results: Based on 82 subjects included, 66 subjects (80.5%) had obstructive sleep apnea, and 16 subjects (19.5%) did not have it. There was a significant difference in PAWP between patients with and without OSA (p value <0.01). Ten subjects OSA (12.1%) had diastolic dysfunction, while all non-OSA subjects had normal diastolic function, with no statistical significance between two groups (p value = 0.20). Diastolic dysfunction significantly associated with PAWP measured using proposed formula  (R = 0.240, p value = 0.030). Conclusion: The new formula could be used to indirectly calculate PAWP and predict diastolic dysfunction in OSA. Obstructive sleep apnea is associated with elevated PAWP. The increased risk of diastolic dysfunction in OSA, especially in obesity patient may indicate for the risk of cardiovascular morbidities.